The effects of acute stress on retrieval of visual and spatial material - Du Plooy, Christopher P (Department of Psychology, 2015)
Previously published studies, using human and non-human animal samples, suggest that stress impairs memory retrieval. However, most human studies that report these impairing effects explore verbal memory only. The aim of the studies reported in this dissertation was to explore the effects of an acute stressor (Study 1), and of administration of prednisone (Study 2), on retrieval of visual-spatial material (both emotional and neutral), and to compare the findings against three theories that attempt to account for the effects of stress on memory: the inverted-U hypothesis (de Kloet et al., 1999), hot-cool theory (Jacobs & Metcalfe, 1998), and the integrated vertical and horizontal perspective theory (Schwabe et al., 2012). To explore the research question, I aimed to systematically replicate, in humans, the pioneering study of de Quervain et al. (1998). They demonstrated that both stress (in the form of foot-shocks) and glucocorticoid treatment impaired memory retrieval, as demonstrated by water maze performance, in rodents. To replicate their design for use in humans, I needed to make several apparatus substitutions. Hence, before embarking on the major studies that constitute the dissertation, I undertook two pilot/preparation studies. Study A verified that a novel visual and spatial task (a virtual environment (VE) water maze task) was a suitable human analog for the Morris Water Maze. Twenty-four participants learned the location of a target in three different VE rooms. Landmarks in the first room were neutral non-arousing pictures; in the second, pleasant arousing pictures; and in the third, unpleasant arousing pictures. Emotional content of landmarks did not affect place learning, although the women demonstrated better recognition for arousing than neutral landmarks. Study B verified that a novel laboratory-based stressor was a suitable substitute for the foot-shock stressor. This novel stressor combines the Cold Pressor Test with the Trier Social Stress Test (TSST) into a single procedure: the Fear Factor Stress Test (FFST). Ninety participants completed one of three conditions: FFST-Stress, FFST-Control, or TSST. The FFST-Stress induced a more robust and sustained cortisol response than the TSST (without increasing participant discomfort), while the FFST-Control condition did not provoke a cortisol response. Following these validation studies, Study 1 explored the effects of the FFST on memory retrieval for the VE rooms created in Study A. Sixty participants learned the location of an invisible target in the VE rooms and, 24 hours later, after undergoing either the FFST-Stress or -Control conditions, completed a set of navigational, recall, and recognition memory tests. In Study 2, the FFST conditions were substituted by a 25mg prednisone dose and a placebo. Following ingestion of the prednisone/placebo, 60 participants completed the same set of navigational and memory tests. Results revealed that neither acute stress nor prednisone administration impaired visual and spatial memory. However, exposure to the acute stressor appeared to enhance verbal memory in women, and prednisone administration appeared to impair verbal memory in both men and women. Relating the current findings to theory revealed that only the inverted-U hypothesis was capable of accounting for the observed pattern of data with regard to verbal memory. Specifically, congruent with predictions derived from that theory, a combination of low levels of endogenous cortisol due to the time of day when procedures were performed, along with the dose-dependent effects of cortisol, might account for the contrasting verbal memory findings seen across Studies 1 and 2. However, none of the three theories were capable of explaining the absence of stress effects on visual and spatial memory. Findings from Studies 1 and 2 therefore suggest that being exposed to an acute stressor or being administered prednisone might have had varying effects across memory domains, which is consistent with a functional perspective on memory. These findings indicate that further investigation into domain-specific effects of stress on memory might be a rewarding area of inquiry.